Talk by Chairman of the Board of Trustees (Institutional Knowledge at Singapore Management University, 2000)
Ho Kwon Ping, Chairman of the Board of Trustees speaking to the pioneer class of Singapore Management University undergraduate students at the Singapore Art Museum on 19 July 2000.